The impact of environmental factors during maternal separation on the behaviors of adolescent C57BL/6 mice - Shin, Sangyep; Lee, Sukwon (Frontiers in Molecular Neuroscience, 2023)
Neonatal maternal separation is a widely used method to create an early life stress model in rodents. This involves separating pups from their mother for several hours each day during the first two weeks of life, resulting in adverse early life experiences. It is known that maternal separation can cause significant impacts on behavior and psychological health, such as anxiety and depression, in adolescent offspring. However, environmental conditions during maternal separation can differ, such as the presence of other animals or replacement with a different dam. To investigate differential effects of various conditions of maternal separation, we designed the following groups,1) moving pups to the isolated room where there are no other adult mice in a nearby cage (iMS), 2) exchanging the dam randomly (eDam), 3) moving pups to the other cage with the bedding material containing maternal odor (olfactory stimulation, OF), and 4) moving pups to another vivarium (MS). From postnatal day (PND) 2 to 20 for 19 consecutive days, pups were separated from the dam daily for 4 hours in the various environments (MS, iMS, eDam, and OF) or were left undisturbed (CON). A series of behavioral assessments were conducted to evaluate locomotion, anxiety, recognition, learning, and memory in adolescent offspring. Results showed that neonatal maternal separation led to deficits in recognition memory, motor coordination, and motor skill learning across all groups. However, the iMS group exhibited anxiety-like behavior in the elevated plus maze test and enhanced extinction of fear memory in the auditory fear conditioning test. The OF and eDam groups displayed partially recovered short-term working memory in the Y-maze test, but exhibited opposite exploratory behaviors; the OF group spent more time in the center while the eDam group spent less. These findings demonstrate that environmental factors during maternal separation cause behavioral alterations in adolescent offspring, providing a potential explanation for the variation in behavioral phenotypes observed in early life stress models.